Bioactive Peptides - Are There More Antihypertensive Mechanisms Beyond ACE Inhibition? - Marques, Claudia; Manuela Amorim, Maria; Odila Pereira, Joana; Estevez Pintado, Manuela; Moura, Daniel; Calhau, Conceicao; Pinheiro, Helder (Current Pharmaceutical Design, 2012)
Diet has a high relevance in health. Hypertension is a major risk factor for cardiovascular diseases and has an important impact on public health, and consequently on countries economy. Scientific research gathered strong evidence about the role of several dietary factors either in etiology or in treatment/prevention of these diseases. Peptides from different food matrices have been studied, and indicated as compounds with particular interest in the context of hypertension. The classical approach involves the identification of peptides with an in vitro ACE inhibitory activity and the assumption that the observed in vivo effects are due to this enzyme blockade. However, in some cases the potency of ACE blockade does not correlate with the antihypertensive activity in vivo. This paper reviews the current literature that identifies mechanisms of action, other than ACE inhibition, that might explain antihypertensive effects of biologically active peptides from different food sources.
Keywords: ACE